2016
DOI: 10.1155/2016/1693704
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Hemodynamic Parameters in Low Risk Pregnancies: Doppler Velocimetry of Uterine, Umbilical, and Middle Cerebral Artery

Abstract: Objective. To elaborate curves of longitudinal reference intervals of pulsatility index (PI) and systolic velocity (SV) for uterine (UtA), umbilical (UA), and middle cerebral arteries (MCA), in low risk pregnancies. Methods. Doppler velocimetric measurements of PI and SV from 63 low risk pregnant women between 16 and 41 weeks of gestational age. Means (±SD) for intervals of gestational age and percentiles 5, 50, and 95 were calculated for each parameter. The Intraclass Correlation Coefficients (ICC) were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 29 publications
2
15
1
1
Order By: Relevance
“…Similar results were obtained when we compared PI and RI before and after UF in this gestational period with reference value in normal pregnancy (5th, 50th, and 90th percentile) to the same gestational age 7,8 (P > 0.05-Kruskal-Wallis test) ( Figure 1).…”
Section: Resultssupporting
confidence: 80%
“…Similar results were obtained when we compared PI and RI before and after UF in this gestational period with reference value in normal pregnancy (5th, 50th, and 90th percentile) to the same gestational age 7,8 (P > 0.05-Kruskal-Wallis test) ( Figure 1).…”
Section: Resultssupporting
confidence: 80%
“…These decreasing patterns of values were in agreement with other studies (Bahlmann, Fittschen, Reinhard, Wellek, & Steiner, 2012;Tavares et al, 2013). In contrast, the results of Figueira et al (2016) showed the same trend of decreasing values for 5 th and 50 th percentile, but no regular pattern was found for the 95 th percentile.…”
Section: Discussionmentioning
confidence: 65%
“…Characteristics of the population analyzed would be responsible for the variability in these values. Despite the fact of being minor, these variations could imply some mistakes about the fetal wellbeing, although the influence of population or ethnic characteristics in pregnancy Doppler parameters should be checked (Figueira et al, 2016). These minor variations were observed due to several reasons include: i) inconsistent choice of the wall filter, ii) divergent size of the sample volumes, iii) manual or automatic curve analysis, iv) varying size of the patient populations, v) different mathematical methods for the calculation of ranges, vi) variations in the application of the Doppler technologies, vii) and varying observation intervals.…”
Section: Discussionmentioning
confidence: 99%
“…During contraction, intramyometrial pressure (IMP) increases and flow through the spiral arteries decreases from 70 mmHg to zero when the intrauterine pressure exceeds 35 mmHg [8,9]. With the cessation of contraction the flow through the uterine spiral arteries, it resumes and returns to normal at the end of the contraction [9,10]. This is reflected in the fetal cerebral circulation by a decreased fetal rSO 2 at rest to an average of 53.3% (42-62%), to a value of 16.3% (15-21%) during the complete contraction, and returning to the initial value at the end of contraction ( fig.1).…”
Section: Results and Discutionsmentioning
confidence: 99%